Peningkatan Kemampuan Perencanaan Karier Peserta Didik Melalui Bimbingan Karier - Wirastiani Binti Yusup (Pusat Kajian Bimbingan dan Konseling FIPPS Unindra, 2024)
Career planning is very important for all students before entering the world of work. Therefore all students need to plan their careers well. The purpose of this study was to analyze the improvement of students' career planning abilities through career guidance services at Kasongan Christian High School. The type of research used is Classroom Action Research. Data collection techniques using observation, interviews, and document studies. The subjects of this study consisted of school principals and students. The research phase is only carried out through two actions. Based on the research conducted, the results show that career guidance services can improve the career planning skills of Kasongan Christian High School students. The results showed that there was an increase in students' career planning abilities from the Low category to the Good category. In the first cycle of action, the results were obtained a) the accuracy of the reasons for choosing a job was 56%, b) the accuracy of the reasons for choosing a tertiary institution was 43%, c) the accuracy of the reasons for choosing a higher education major was 18%, and d) the accuracy of the reasons for choosing a major in SMA was 37 %. While Cycle II obtained the results: a) the reason for choosing a job was 81%, b) the reason for choosing a college was 68%, c) the reason for choosing a major was 75%, and d) the reason for choosing a major was high school by 56%.Keywords: Career Planning, Career Guidance